Analisis Pengelolaan Wakaf Uang pada Koperasi Jasa Keuangan Syariah (Pendekatan Analytical Network Process) - Arie Haura; Lukman M Baga; Hendri Tanjung (AL-MUZARA'AH, 2015)
This study describes the process of Sharia Financial Service Cooperation (KJKS) becoming nazhir waqf, analyzing the priorities of internal and external factors which related with cash waqf. This research uses descriptive quantitative and qualitative approach based on study literature, observation, and quetionaire using analytical network process (ANP) method. The internal factors and external factors devided into 8 cluster. 2 General Cluster and 6 Detailed Cluster: cluster of Internal Aspect, cluster of External Aspect, cluster of SDM KJKS, cluster of Accountability, cluster of Product, cluster of Regulation, cluster of Demography, and cluster of Civil Sociaty. The calculations showed that the highest score which is greatly affect the cash waqf management in KJKS from Internal Aspect such as: Cluster of Accountability (36%), Cluster of Product (33%), and Cluster of SDM KJKS (31%). External Aspect such as: Cluster of Regulation (38%), cluster of Civil Sociaty (37%), and cluster of Demography (25%). Furthermore, the important priority from detailed cluster are Asset Accumulation element (22,8%) and Requirement of Sharia Principle (22,9%).